Right Atrial and Ventricular Collapse After Cardiopulmonary Resuscitation. Issue 15 (January 2021) - Douedi, Steven; Meleka, Matthew; Daniels, Steven
Prompt and effective chest compressions is the cornerstone cardiopulmonary resuscitation and has been found to improve cardiac arrest outcomes. Despite being rare, a wide variety of cardiac and pulmonary complications due to chest compressions have been identified. We present a case of a young, otherwise healthy female developing toxic shock syndrome and ultimately cardiac arrest requiring chest compressions found to cause right atrial and ventricular collapse on echocardiography.